KANDUNGAN MINERAL DAN LOGAM BERAT PADA GARAM YANG DIEKSTRAK DARI RUMPUT LAUT Sargassum sp. MENGGUNAKAN METODE DIBILAS DAN DIRENDAM - Wilma Nur Laily; Munifatul Izzati; Sri Haryanti (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Seaweed Sargassum sp. containing salt which generally has better quality than table salt. This salt is called biosalt. The advantage of biosalt is that it contains high and low K, this biosalt can be used as an alternative for people with hypertension. In addition to producing K and Na biosalt seaweed also contains several minerals that are beneficial for those of you who need it. This study aims to determine the content of macro minerals (Ca and Mg), micro minerals (Fe, Mn and Zn) and heavy metals (Pb and Cu) in the salt of Sargassum sp. The extraction method used is rinsed and soaked with 3 replications. The results of the salt extraction were analyzed for the mineral and heavy metal content using ICP-OES, then with mineral and heavy metal minerals in the crystal of Crush. The results showed that mineral and mineral minerals in the extraction of Sargassum sp. has a higher value than table salt, the weight of heavy metals Pb and Cu is lower than that of table salt and also meets the requirements of organic materials according to SNI 01-3556-2000. The results of this study can be concluded that the salt content of Sargassum sp. have higher nutrition than krosok salt and also safe if consumed. Keywords: Biosalt,heavy metals, ICP-OES, minerals, Sargassum sp.